Emergency Prenatal Telemonitoring System in Wireless Mesh Network - Muhammad Haikal Satria; Jasmy bin Yunus; Eko Supriyanto (Universitas Ahmad Dahlan, 2014)
Telemedicine promises a great opportunity for health care service improvement. However, it has several issues for its implementation in certain area. They include communication service quality, infrastructure and operational cost. Since Wireless Mesh Network (WMN) is designed to reduce the infrastructure cost and operational cost, an investigation of network performance for implementation of telemedicine is required. In this paper, a simulation to investigate the wireless mesh network quality of service. Using network simulator 2, The QoS performance analysis was performed in different routing protocol scenarios of proposed system. It showed that OLSR protocol for Mesh Network maintained the time transfer of the EPT data. The field testing of the proposed system to measure the distance with various time has already been done. The infrastructure has been also implemented using low cost 5.8 GHz transceiver for backhauls and low cost 2.4 GHz transceiver for clients. Test result shows that the low cost telemedicine system is able to do real time communication between patient and medical staff with medical data rate up to 2 Mbps. It shows that telemonitoring system using wireless mesh network can give a low cost application in emergency time with acceptable medical data transfer quality.